Redesign of Conjugate Cam of Rotation Variable Speed Mechanism of Electronic Dobby - Zhang Yuanhua; Gou Xiangfeng; Chen Xiaofang; Wang Zonglu (Jixie chuandong)
In order to obtain the precise contour of the conjugate cam of the rotation variable speed mechanism of the STAUBLI type electronic dobby,the data of original conjugate cam profile and other main parts of the mechanism is measured,the 3D solid model of rotation variable speed mechanism is established based on CREO software and the kinematics simulation analysis is carried out. Then the angular displacement,angular velocity as well as angular acceleration curves of the follower are obtained before the redesign. From the angle of the kinematics design,based on the theoretically derivate conjugate cam contour line of mathematic model,the conjugate cam curve equation is redesigned,the equation is solved numerically and the theoretical conjugate cam contour curve is reached out. After that,conjugate cam 3D solid model is set up on the basis of theoretical contour curve and is plugged to the rotation variable speed mechanism to present kinematics simulation analysis.The analysis results show that the movement curve of redesigned conjugate cam is smooth,which is satisfied with the working requirements.